2007
DOI: 10.1002/tox.20283
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective efficacy of certain flavonoids against microcystin induced toxicity in mice

Abstract: Toxic cyanobacteria (blue-green algae) water blooms have become a serious problem in several industrialized areas of the world. Microcystin-LR (MC-LR) is a cyanobacterial heptapeptide that represents acute and chronic hazards to animal and human health. Identification of suitable chemprotectants against microcystin is essential considering human health hazards. In the present study, we have evaluated the protective efficacy of three flavanoids namely quercetin (200 mg/kg), silybin (400 mg/kg), and morin (400 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 31 publications
2
47
0
1
Order By: Relevance
“…Silymarin is a bioactive extract of the fruits of milk thistle (Silybum marianum), containing seven flavolignans with reported antitumor and hepatoprotective properties [149,150]. Three of these compounds, silybin A, silybin B, and isosilybin A have been extracted as fermentation products of a strain of Aspergillus iizukae isolated from the leaves of S. marianum.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Silymarin is a bioactive extract of the fruits of milk thistle (Silybum marianum), containing seven flavolignans with reported antitumor and hepatoprotective properties [149,150]. Three of these compounds, silybin A, silybin B, and isosilybin A have been extracted as fermentation products of a strain of Aspergillus iizukae isolated from the leaves of S. marianum.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Silybum marianum seeds contain more than seven fl avonolignans. Many studies have reported the biological evaluation of silymarin, such as in cancer chemoprevention and hepatoprotection (1,2). Silymarin has the ability to scavenge free radicals, it has been found to increase the production of glutathione in hepatocytes and the activity of superoxide dismutase in erythrocytes (3).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that silibinin exhibited an anti-apoptotic effect on isoproterenol-treated rat cardiac myocytes by reducing the expression of inducible nitric oxide synthase (iNOS) (7) and by increasing superoxide dismutase (SOD) activity (8). Subsequently, silibinin was detected to promote sustained superoxide (O 2 •− ) production, which had a protective effect, as exogenous SOD markedly enhanced silibinininduced apoptosis (9). In this study, silibinin displayed a cytotoxic effect on human fibroblast cells HT1080 through induction of reactive oxygen species (ROS) generation.…”
Section: Introductionmentioning
confidence: 99%